Analysis Impementation of PSAK 101 Presentation of Financial Statements of Financial Statements in Sharia at BMT Ummat Mandiri Balikpapan - Julianti, Utamy; Mardatillah, Mardatillah (JEMI is managed and published by the Management Study Program, Faculty of Economics and Business, Kutai Kartanegara University. Institutional legality is reflected in the ISSN number: 1411-9560 published by LIPI in 2003 as a manifestation of the comm, 2019)
Nowdays, BMT not just finance entitas but growing as shariah finance entitas. Its mean BMT have more power to growing. Aspecially implementation accounting standars in sharia. In fact not many finance sharia institution using a PSAK. The purpose of this study was to determine wheater accounting standars play a role in the management of the financial statements BMT Ummat Mandiri Balikpapan.The study used a qualitative descriptive research. For data collection is done by techiques of documentation and interview techniques. The data used is BMT Ummat Mandiri Fincancial Statement consisting of balance sheet, income statement and cash flow statement with the 2011-2013. This study uses two variables consisting of PSAK 101 independent variables and the dependent variable is the financial statements. This study was done by analyzing the financial statements of the BMT Ummat Mandiri whether in accordance with PSAK 101 or not.The result of this study show the presentation of financial statements BMT Ummat Mandiri complete the take because it does not present all the components of the financial statements are in PSAK 101, but for the presentation of the balance sheet, income statement and cash flow statement presented in accordance with PSAK 101. Method of recording recognition of the financial statement have been prepared on BMT Ummat Mandiri accrual basic, for the calculation of income available for the result are presented using the cash basis.Keyword : BMT Ummat Mandiri, Implemetation PSAK 101, finance shariah